Relationship between Molecular Structure and Gelling Properties of Rice Starch from Different Production Regions - ZOU Penglai, ZHANG Jiale, LI Zhuo, ZHANG Longxin, ZHOU Bin, WU Wenjin, CHU Shang (Shipin Kexue)
The chain length distribution, basic physicochemical properties, and gelling properties of rice starches from 10 different regions were analyzed. The results showed that the amylose content was closely related to the pasting, thermal, and textural properties. Furthermore, significant differences were observed in relative crystallinity and molecular ordering among all starch samples. Rice starch from Yuanyang, Henan had the highest amylose content and exhibited better gel strength. The chain length distribution of amylopectin varied significantly among different rice starch samples, with the proportions of A (degree of polymerization (DP) 6–12), B1 (DP 13–24), B2 (DP 25–36), and B3+ (DP ≥ 37) chains being 25.03%–30.90%, 47.82%–52.02%, 10.17%–11.98%, and 8.39%–12.56%, respectively. Pearson correlation analysis was used to investigate the relationship between the molecular structure and properties of rice starch. It was found that the rheological behaviors of amylopectins with different chain lengths dispersed in water were different. The proportion of medium and long chains (DP 13–24) was negatively correlated with the transition temperature, and the proportion of short chains (DP 6–12) was positively correlated with the gel hardness. The results of this study contribute to understanding the physicochemical and gelling properties of starch based on its fine structure, and consequently selecting starch products for production targets and market demands.